Bayesian regression analyses of radiation modality effects on pericardial and pleural effusion and survival in esophageal cancer. Issue 1 (October 2016) - He, Liru; Chapple, Andrew; Liao, Zhongxing; Komaki, Ritsuko; Thall, Peter F.; Lin, Steven H.
Abstract: Background and purpose: To evaluate radiation modality effects on pericardial effusion (PCE), pleural effusion (PE) and survival in esophageal cancer (EC) patients. Materials and methods: We analyzed data from 470 EC patients treated with definitive concurrent chemoradiotherapy (CRT). Bayesian semi-competing risks (SCR) regression models were fit to assess effects of radiation modality and prognostic covariates on the risks of PCE and PE, and death either with or without these preceding events. Bayesian piecewise exponential regression models were fit for overall survival, the time to PCE or death, and the time to PE or death. All models included propensity score as a covariate to correct for potential selection bias. Results: Median times to onset of PCE and PE after RT were 7.1 and 6.1 months for IMRT, and 6.5 and 5.4 months for 3DCRT, respectively. Compared to 3DCRT, the IMRT group had significantly lower risks of PE, PCE, and death. The respective probabilities of a patient being alive without either PCE or PE at 3-years and 5-years were 0.29 and 0.21 for IMRT compared to 0.13 and 0.08 for 3DCRT. In the SCR regression analyses, IMRT was associated with significantly lower risks of PCE (HR = 0.26) and PE (HR = 0.49), and greater overall survival (probability of beneficial effect ( pbe ) > 0.99), after controlling for known clinical prognostic factors. Conclusions: IMRT reduces the incidence and postpones the onset of PCE and PE, and increases survival probability, compared to 3DCRT.